ANALISIS HUKUM TERKAIT DEFINISI TERORISME BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2018 TENTANG PEMBERANTASAN TINDAK PIDANA TERORISME - Doni Wijaya Munte; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the problems of the world, including those who oppose the Indonesian nation today, is the crime of terrorism. Terrorism as an extraordinary crime (extraordinary crime) that is still very difficult to handle. Terrorism is one of the best in the world and includes Indonesia. The world community ceaselessly condemns behavior that makes people afraid of trauma and fear. Terrorism is a form of crime that needs financial assistance and the need for weapons and explosives. With these characteristics it causes many difficulties in developing terrorism. In Law Number 5 of 2018 concerning Amendments to Law Number 13 of 2003 concerning the Establishment of Government Regulations in lieu of Law Number 1 of 2002 concerning Eradication of Terrorism Crimes in article 1 number (2) Fighting, Fighting, Fighting, Fighting , Fight, Fight, Fight, Fight, Fight, Fight, Fight, Fight, Fight, Fight, Protect, Fight Security. Which in this definition still causes a lot of interpretations and problematic phrases. This type of research is a normative legal research that uses literature studies in finding data. This research is descriptive in nature which tries to provide the data set by the researcher and the details of the existing debate. In selecting this research using qualitative data analysis which is intended to explain and assess the data that has been collected by the author. This lesson uses secondary data or scientific data that has been codified. The results of this study are explaining the theory of defining terrorism in the Law on Combating Criminal Acts of Terrorism which still involves many interpretations and phrases that are problematic in the definition of terrorism. How to overcome rigidity in society or enforce the law in terms of overcoming and eradicating criminal acts of terrorism. Because the unclear definition of terrorism that is needed can be distorted certain people who are not responsible which ones can not carry out terrorism into acts of terrorism as the definition of terrorism. Which must be issued This law must provide protection and security for everyone. Keywords: Legal Analysis - Related to the Definition - Law - Eradication of Terrorism Criminal Acts.